FRI0586 THE EFFECT OF TOCILIZUMAB IN THE PREVENTION OF FAMILIAL MEDITERRANEAN FEVER ATTACKS. (June 2019) - Colak, Seda; Tekgoz, Emre; Çınar, Muhammet; Yilmaz, Sedat
Abstract : Background: Familial Mediterranean Fever (FMF) is the most frequent hereditary autoinflammatory disease in the worldwide. Colchicine is the mainstay of the treatment that is used for both preventing the attacks and developing amyloidosis. In case of colchicine resistance, which constitutes almost 5% of all patients, there are some alternatives such as anti-TNF agents, IL-6 and IL-1 antagonists. These agents have also been used in patients with established amyloidosis secondary to FMF. Tocilizumab (TCZ), an IL-6 receptor antagonist, although is effective in the treatment of amyloidosis, little known about its effectiveness in the preventing of febrile attacks. Objectives: In this study, we aimed to find out whether TCZ therapy decrease the frequency of recurrent attacks of FMF or not. Methods: This retrospective cross-sectional study designed in a tertiary rheumatology clinic between the years 2009 and 2019. A total of 15 patients were given intravenous TCZ at a dose of 8mg/kg/month, to improve amyloidosis associated with FMF. Data of demographic and clinical characteristics of patients were obtained retrospectively from patient files. Results: Three female and 12 male patients received TCZ for amyloidosis treatment. The mean age of patients was 42.07±14.37 years and disease duration was 25.73±10.86 years. All of the patients had biopsy results providing amyloidosis. According to international severity scoring system for FMF, all of the patients had severe disease. Demographic and clinical data were shown in Table 1 . The frequency of attacks was evaluated during TCZ treatment, and it was reported that 1 patient had no response, 6 patients had decreased attack frequency and 8 patients had no attacks. Serious adverse events were seen in none of the patients. MEFV:Mediterranean Fever, TCZ:Tocilizumab Conclusion: Tocilizumab is found to be effective on improvement of amyloidosis. In the current analysis, we found that TCZ also decreases the frequency of recurrent attacks in patients with FMF. Besides, TCZ is well tolerated among the patients. Further and prospective studies with larger sample are needed to support these results. References: [1] Yilmaz S, Cinar M, Simsek I, Erdem H, Pay S. Tocilizumab in the treatment of patients with AA amyloidosis secondary to familial Mediterranean fever. Rheumatology2015;54:564-565 Disclosure of Interests: None declared